Lipophilic Peptide Dendrimers for Delivery of Splice-Switching Oligonucleotides - Haneen Daralnakhla; Osama Saher; Susanna Zamolo; Safa Bazaz; Jeremy P. Bost; Marc Heitz; Karin E. Lundin; Samir EL Andaloussi; Tamis Darbre; Jean-Louis Reymond; Rula Zain; C. I. Edvard Smith (MDPI AG, 2021)
Non-viral transfection reagents are continuously being developed in attempt to replace viral vectors. Among those non-viral vectors, dendrimers have gained increasing interest due to their unique molecular structure and multivalency. However, more improvements are still needed to achieve higher efficacy and lower toxicity. In this study, we have examined 18 peptide dendrimers conjugated to lipophilic moieties, such as fatty acids or hydrophobic amino acids, that were previously explored for siRNA. Reporter cells were employed to investigate the transfection of single strand splice-switching oligonucleotides (ONs) using these peptide dendrimers. Luciferase level changes reflecting efficiency varied with amino acid composition, stereochemistry, and complexation media used. 3rd generation peptide dendrimers with D-amino acid configuration were superior to L-form. Lead formulations with 3rd generation, D-amino acid peptide dendrimers increased the correction level of the delivered ON up to 93-fold over untreated HeLa Luc/705 cells with minimal toxicity. To stabilize the formed complexes, Polyvinyl alcohol 18 (PVA18) polymer was added. Although PVA18 addition increased activity, toxicity when using our best candidates G 2,3KL-(Leu)4 (D) and G 2,3KL-diPalmitamide (D) was observed. Our findings demonstrate the potential of lipid-conjugated, D-amino acid-containing peptide dendrimers to be utilized as an effective and safe delivery vector for splice-switching ONs.